Piezoelectric biosensors for real-time monitoring of hybridization and detection of hepatitis C virus - Skladal, P.; Riccardi, C. D.; Yamanaka, Hideko [UNESP]; da Costa, P. I. (Elsevier B.V., 2004)
The piezoelectric quartz crystal resonators modified with oligonucleotide probes were used for detection of hepatitis C virus (HCV) in serum. The gold electrodes on either rough or smooth surface crystals were modified with a self-assembled monolayer of cystamine. After activation with glutaraldehyde, either avidin or streptavidin were immobilized and used for attachment of biotinylated DNA probes (four different sequences). Piezoelectric biosensors were used in a flow-through setup for direct monitoring of DNA resulting from the reverse transcriptase-linked polymerase chain reaction (RT-PCR) amplification of the original viral RNA. The samples of patients with hepatitis C were analyzed and the results were compared with the standard RT-PCR procedure (Amplicor test kit of Roche, microwell format with spectrophotometric evaluation). The piezoelectric hybridization assay was completed in 10 min and the same sensing surface was suitable for repeated use. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: piezoelectric biosensor; hepatitis C virus; RT-PCR